Copper paste and method for manufacturing copper paste

By adjusting the ratio of copper particles to reducing agent, the copper paste can be sintered in the air for a short time at low temperature, solving the problems of difficulty in sintering copper paste and the hazards of decomposition of reducing agents in the prior art, and obtaining excellent conductivity and safety.

CN119274843APending Publication Date: 2025-01-07CHANGZHOU JUHE NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310814065.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the sintering of copper paste under short-term conditions in the air under low temperatures, and the reducing agent in the metal paste may decompose during the heating process, resulting in health hazards.

Method used

Copper paste with copper particles, reducing agent and dispersion medium is used to adjust the ratio of copper particles mass, average particle size and reduction dose (R1² × m2/m1 = 0.008~0.8), and the low temperature and short-term sintering is achieved in the air, and the The appropriate copper hydride layer forms excellent conductivity, reducing the reduction dose to reduce health hazards.

Benefits of technology

Excellent conductive sintering of copper paste under low temperature and short-term conditions in the air is achieved, which reduces the health hazards caused by decomposition of reducing agents, and improves the oxidation resistance and conductivity of copper paste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004321224160000111
    Figure BDA0004321224160000111
Patent Text Reader

Abstract

Provided are: a copper paste which is capable of achieving excellent electrical conductivity even when sintered in an air atmosphere under low-temperature and short-time conditions; and a method for producing the copper paste. Also provided are: a copper paste which is capable of improving health hazards caused by the decomposition of a reducing agent in a metal paste; and a method for producing the copper paste. This copper paste contains copper particles, a reducing agent, and a dispersion medium, and the ratio represented by formula (1) is 0.008-0.8, where m1 is the mass of the copper particles, R1 is the average particle diameter of the copper particles, and m2 is the mass of the reducing agent. Formula (1): R12 * m2 / m1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper paste and a method for producing the copper paste. Background Art

[0002] In the HJT cell structure which is one of the structures of a crystalline solar cell, a method of forming electrodes at 200° C. or less using a silver paste having a thermosetting resin such as an epoxy resin as a binding material is widely known.

[0003] However, since the conductive component is silver, which is a precious metal, there is a concern about the supply limit as solar cells become more popular. In addition, silver itself is expensive, which is the reason for the high price of solar cells themselves. In order to further popularize solar cells, it is required to use materials other than silver.

[0004] As an alternative, a copper paste using copper particles has been studied, but it is difficult for copper particles to be sintered in air to form an electrode.

[0005] In order to solve the above-mentioned problem, a method of coating the copper surface with silver has been proposed. However, it is difficult to achieve a low price because of the additional process for the silver coating.

[0006] Patent Document 1 proposes copper hydride nanoparticles in which the surface of copper particles is coated with a long-chain organic compound. However, since the surface is coated with a long-chain organic compound, sintering is difficult, and the conductivity of the metal film after sintering is insufficient.

[0007] In order to solve this disadvantage, a method for producing copper hydride nanoparticles without using a long-chain organic compound and a composition of a metal paste using the production method are disclosed in Patent Document 2. In the composition of the metal paste, it is necessary to mix copper hydride nanoparticles and a metal filler containing copper.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent document 1: International Patent Publication No. 2004 / 110925

[0011] Patent Document 2: International Publication Patent 2009 / 098985 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] However, in the manufacturing method of Patent Document 2, sintering in air cannot be achieved. Therefore, Patent Document 2 only discloses sintering in a nitrogen atmosphere and resistance value measurement. The present invention is made in view of the above-mentioned problems, and provides a copper paste that can achieve excellent conductivity even when sintering is performed in an air atmosphere under low temperature and short time conditions, and a method for manufacturing the copper paste.

[0014] In addition, if a reducing agent is added to the metal paste, the reducing agent may decompose during the heating and sintering process of the metal paste, and there is a concern that the decomposition gas generated thereby may harm the health of the operator. In addition, the present invention provides a copper paste capable of improving the health hazard caused by the decomposition of the reducing agent in the metal paste, and a method for producing the copper paste.

[0015] Technical means to solve technical problems

[0016] In view of the above problems, the present invention has conducted in-depth research and found a copper paste that can be sintered in an air atmosphere at a low temperature and in a short time. The copper paste comprises copper particles, a reducing agent and a dispersion medium. When the mass of the copper particles is set to m1, the average particle size of the copper particles is set to R1, and the mass of the reducing agent is set to m2, formula (1): R1 2 The present invention was completed by finding that the ratio represented by ×m2 / m1 was 0.008 to 0.8.

[0017] That is, the above-mentioned problem of the present invention can be solved by the following technical means.

[0018] 1. A copper paste comprising copper particles, a reducing agent and a dispersion medium,

[0019] When the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, the ratio represented by the following formula (1) is 0.008 to 0.8,

[0020] Formula (1): R1 2 ×m2 / m1.

[0021] 2. The copper paste according to item 1 above, wherein

[0022] The copper particles have an average particle size of 1.0 to 5.0 μm.

[0023] 3. The copper paste according to item 1 above, wherein

[0024] The content of the reducing agent is 0.1 to 15% by mass relative to the total mass of the copper paste.

[0025] 4. The copper paste according to item 1 above, wherein

[0026] The copper particles include copper particles coated with copper hydride.

[0027] 5. The copper paste according to item 1 above, wherein

[0028] The content of the copper hydride coated on the copper particles is 0.1% by mass or more relative to the mass of the copper particles.

[0029] 6. The copper paste according to item 1 above, wherein

[0030] The reducing agent is metal hydride and / or hypophosphorous acid.

[0031] 7. The copper paste according to item 6 above, wherein

[0032] The metal hydride is selected from lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, and calcium hydride.

[0033] 8. The copper paste according to item 1 above, wherein

[0034] The above dispersion medium is a liquid dispersion medium.

[0035] 9. The copper paste according to item 8 above, wherein

[0036] The liquid dispersion medium is a polar liquid dispersion medium.

[0037] 10. The copper paste according to item 9 above, wherein

[0038] The polar liquid dispersion medium is selected from water, glyceryl ether, glyceryl ether acetate, alcohol and a mixture thereof.

[0039] 11. The copper paste according to item 9 or 10 above, wherein

[0040] The polar liquid dispersion medium is water.

[0041] 12. The copper paste according to item 1 above, wherein

[0042] The content of the dispersion medium is 1 to 100% by mass relative to the mass of the copper particles.

[0043] 13. The copper paste according to the above item 1, further comprising a resin binder.

[0044] 14. The copper paste according to item 13 above, wherein

[0045] The content of the resin binder is 0.001 to 10% by mass relative to the mass of the copper particles.

[0046] 15. A method for producing the copper paste according to item 1 above, comprising:

[0047] A step of dispersing copper particles in a dispersion medium; and

[0048] The process of adding reducing agent,

[0049] When the amount of copper particles used is m1, the average particle size of the copper particles is R1, and the amount of the reducing agent used is m2, the ratio represented by the following formula (1) is 0.008 to 0.8,

[0050] Formula (1): R1 2 ×m2 / m1.

[0051] 16. The method for producing a copper paste according to item 15 above, wherein:

[0052] The copper particles have an average particle size of 1.0 to 5.0 μm.

[0053] 17. The method for producing a copper paste according to item 15 above, wherein:

[0054] The reducing agent is used in an amount of 0.1 to 15% by mass relative to the total mass of the copper paste.

[0055] 18. The method for producing a copper paste according to item 15 above, wherein:

[0056] The reducing agent is metal hydride and / or hypophosphorous acid.

[0057] 19. The method for producing a copper paste according to item 18 above, wherein:

[0058] The metal hydride is selected from lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, and calcium hydride.

[0059] 20. The method for producing a copper paste according to item 15 above, wherein:

[0060] The above dispersion medium is a liquid dispersion medium.

[0061] 21. The method for producing a copper paste according to item 20 above, wherein:

[0062] The above-mentioned liquid dispersion medium is a polar liquid dispersion medium.

[0063] 22. The method for producing a copper paste according to item 21 above, wherein:

[0064] The polar liquid dispersion medium is selected from water, glyceryl ether, glyceryl ether acetate, alcohol and a mixture thereof.

[0065] 23. The method for producing a copper paste according to item 21 or 22, wherein:

[0066] The polar liquid dispersion medium is water.

[0067] 24. The method for producing a copper paste according to item 15 above, wherein:

[0068] The amount of the dispersion medium used is 1 to 100% by mass based on the mass of the copper particles.

[0069] 25. The method for producing the copper paste according to item 15 above, further comprising:

[0070] The process of adding resin binder.

[0071] 26. The method for producing a copper paste according to item 25 above, wherein:

[0072] The resin binder is used in an amount of 0.001 to 10% by mass relative to the mass of the copper particles.

[0073] Effects of the Invention

[0074] According to the present invention, a copper paste that can achieve excellent conductivity even when sintered in an air atmosphere at a low temperature and for a short time, and a method for producing the copper paste can be provided. In addition, a copper paste that can improve health hazards caused by decomposition of a reducing agent in a metal paste, and a method for producing the copper paste can be provided. DETAILED DESCRIPTION

[0075] 1. Copper paste

[0076] The present invention relates to a copper paste for forming an electrode of a solar cell. The copper paste comprises copper particles, a reducing agent and a dispersion medium. In the copper paste, when the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, formula (1): R1 2 The ratio represented by ×m2 / m1 is 0.008 to 0.8. The copper paste having the above constitution can provide an electrode having very excellent oxidation resistance compared to conventional copper pastes and very excellent conductivity even when sintered in an atmosphere containing oxygen (eg, air atmosphere).

[0077] The mechanism of action of the present invention is not yet clear, but can be inferred as described below. When the copper paste is sintered in an air atmosphere, in order to achieve excellent electrical conductivity, it is important to form a copper hydride layer on the surface of the copper particles in an appropriate amount. In addition, the amount of the copper hydride layer formed on the surface of the copper particles is proportionally associated with the mass of the copper particles, the average particle size of the copper particles, and the mass of the reducing agent. That is, by making the mass of the copper particles, the average particle size of the copper particles, and the mass of the reducing agent satisfy a specific proportional relationship, a copper hydride layer can be formed on the surface of the copper particles in an appropriate amount. Thus, an electrode having very excellent electrical conductivity can be obtained even when sintered in an atmosphere containing oxygen (e.g., an air atmosphere). In addition, the copper paste that satisfies the above-mentioned specific proportional relationship can reduce the amount of the reducing agent in the copper paste, thereby improving the health hazards caused by the decomposition of the reducing agent in the copper paste.

[0078] In the copper paste of the present invention, when the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, the formula (1) is: R1 2 The ratio represented by ×m2 / m1 may be 0.008 to 0.8. The lower limit of the ratio represented by the above formula (1) may be 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, 0.03, 0.031, 0.032, 0.033, 0.034, 0.035, 0.036, 0.037, 0.038. The upper limit of the ratio represented by the above formula (1) may be 0.8, 0.79, 0.78, 0.77, 0.76, 0.75, 0.74, 0.73, 0.72, 0.71, 0.7, 0.69, 0.68, 0.67, 0.66, 0.65, 0.64, 0.63, 0.62, or 0.61. In order to further exert the effect of the present invention, the ratio represented by the above formula (1) is preferably 0.01 to 0.79, 0.012 to 0.78, 0.014 to 0.77, 0.016 to 0.76, 0.018 to 0.75, 0.02 to 0.74, 0.022 to 0.73, 0.024 to 0.72, 0.026 to 0.71, 0.028 to 0.7, 0.03 to 0.69, 0.032 to 0.68, 0.034 to 0.67, 0.036 to 0.66, 0.038 to 0.65.

[0079] In the copper paste of the present invention, the average particle size of the copper particles may be 1.0 to 5.0 μm. The lower limit of the average particle size of the copper particles may be 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, or 2.0 μm. The upper limit of the average particle size of the copper particles may be 5.0 μm, 4.9 μm, 4.8 μm, 4.7 μm, 4.6 μm, 4.5 μm, 4.4 μm, 4.3 μm, 4.2 μm, 4.1 μm, or 4.0 μm. In order to further exert the effect of the present invention, the average particle size of the copper particles is preferably 1.1 to 4.9 μm, 1.2 to 4.8 μm, 1.3 to 4.7 μm, 1.4 to 4.6 μm, 1.5 to 4.5 μm, 1.6 to 4.4 μm, 1.7 to 4.3 μm, 1.8 to 4.2 μm, 1.9 to 4.1 μm, 2.0 to 4.0 μm. In addition, in order to exert the effect of the present invention, when the specific range of the ratio shown in the above formula (1) is satisfied, the square of the average particle size of the copper particles and the content of the reducing agent have an inverse proportional relationship. That is, when the specific range of the ratio shown in the above formula (1) is satisfied, by making the average particle size of the copper particles satisfy the above specific range of the present invention, the content of the reducing agent can be reduced to a certain amount or less, and the health hazards caused by the decomposition of the reducing agent can be improved.

[0080] In the copper paste of the present invention, the content of the copper particles may be 5 to 95% by mass relative to the total mass of the copper paste. The lower limit of the content of the copper particles may be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, or 40% by mass. The upper limit of the content of the copper particles may be 94 mass%, 93 mass%, 92 mass%, 91 mass%, 90 mass%, 89 mass%, 88 mass%, 87 mass%, 86 mass%, 85 mass%, 84 mass%, 83 mass%, 82 mass%, 81 mass%, or 80 mass%.

[0081] In the copper paste of the present invention, the copper particles include copper particles coated with copper hydride. The copper hydride includes hydrogen elements, copper atoms are present in a state of being bonded to hydrogen atoms, and can be decomposed into copper and hydrogen by heating (eg, heating at a sintering temperature).

[0082] For the copper paste of the present invention, the content of the copper hydride coated on the copper particles may be 0.01% by mass or more relative to the mass of the copper particles. The lower limit of the content of the copper hydride coated on the copper particles may be 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% by mass.

[0083] In the copper paste of the present invention, the reducing agent can be used as long as it can reduce copper ions. From the viewpoint of good reduction effect of copper ions, metal hydrides and hypophosphorous acid are preferred. As the metal hydride, it can be selected from lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, and calcium hydride, preferably lithium aluminum hydride, lithium borohydride, and sodium borohydride.

[0084] For the copper paste of the present invention, the content of the reducing agent can be 0.1 to 15% by mass relative to the total mass of the copper paste. The upper limit of the content of the reducing agent can be 14% by mass, 13% by mass, 12% by mass, 11% by mass, 10% by mass, 9% by mass, 8% by mass, 7% by mass, 6% by mass, 5% by mass, 4% by mass, and 3% by mass. In order to further exert the effect of the present invention, the content of the reducing agent is preferably 0.1 to 14% by mass, 0.1 to 13% by mass, 0.1 to 12% by mass, 0.1 to 11% by mass, 0.1 to 10% by mass, 0.1 to 9% by mass, 0.1 to 8% by mass, 0.1 to 7% by mass, 0.1 to 6% by mass, 0.1 to 5% by mass, 0.1 to 4% by mass, and 0.1 to 3% by mass.

[0085] In addition, the copper paste of the present invention contains a dispersion medium. From the viewpoint of good dispersibility and obtaining further excellent conductivity, the dispersion medium is preferably a liquid dispersion medium. Compared with a dispersion medium with high viscosity, when a liquid dispersion medium is used, the copper particles can be further uniformly dispersed, and using such a copper paste, a conductive film with uniform thickness can be formed. In addition, the above-mentioned liquid dispersion medium is preferably a polar dispersion medium. The copper particles coated with copper hydride have further good compatibility with the polar liquid dispersion medium. Therefore, compared with a non-polar liquid dispersion medium, when a polar liquid dispersion medium is used, a further uniform dispersion state can be achieved, and a further uniform conductive film can be formed. As a result, the conductivity of the metal film can be further increased. As the above-mentioned polar liquid dispersion medium, it can be selected from water, glycerol ether, glycerol ether acetate, alcohol and a mixture thereof. Specifically, the liquid dispersion medium can be water, alcohol, terpineol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol isopropyl ether, propylene glycol monobutyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, ethylene glycol monohexyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monohexyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, ethylene glycol monoisopropyl ether acetate, ethylene glycol monobenzyl ether acetate, ethylene glycol monohexyl ether acetate, and mixtures thereof. As the alcohol, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, hexanol, cyclohexanol, etc. can be cited. From the viewpoint of further improving dispersibility, as the dispersion medium, water is preferably used. When water is used as the dispersion medium, a more dense and uniform conductive film can be formed when the copper paste is sintered, thereby forming a conductive film with further excellent conductivity.

[0086] In the copper paste of the present invention, the content of the above-mentioned dispersion medium can be 1 to 100 mass% relative to the mass of the above-mentioned copper particles. As the lower limit of the content of the above-mentioned dispersion medium, it can be 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass%, 8 mass%, 9 mass%, 10 mass%, 11 mass%, 12 mass%, 13 mass%, 14 mass%, 15 mass%, 16 mass%, 17 mass%, 18 mass%, 19 mass%, 20 mass%. As the upper limit of the content of the above-mentioned dispersion medium, it can be 99 mass%, 98 mass%, 97 mass%, 96 mass%, 95 mass%, 94 mass%, 93 mass%, 92 mass%, 91 mass%, 90 mass%, 89 mass%, 88 mass%, 87 mass%, 86 mass%, 85 mass%, 84 mass%, 83 mass%, 82 mass%, 81 mass%, 80 mass%. In order to further exert the effect of the invention of the present application, the content of the above-mentioned reducing agent is preferably 1-99 mass%, 2-98 mass%, 3-97 mass%, 4-96 mass%, 5-95 mass%, 6-94 mass%, 7-93 mass%, 8-92 mass%, 9-91 mass%, 10-90 mass%, 11-89 mass%, 12-88 mass%, 13-87 mass%, 14-86 mass%, 15-85 mass%.

[0087] The copper paste of the present invention may or may not contain a binder. In one embodiment, it is preferred that a binder is contained in the copper paste. In one embodiment, it is preferred that no binder is contained in the copper paste. When a binder is contained in the copper paste of the present invention, the adhesion between the obtained metal film and the substrate becomes better, and a metal film with excellent reliability can be obtained. When the copper paste of the present invention does not contain a binder, sintering can be performed at a further low temperature and in a short time. In addition, when the copper paste does not contain a binder, the behavior of the above-mentioned copper particles will not be adversely affected during sintering, and therefore, a further dense and uniform metal film can be formed, and further excellent conductivity can be obtained.

[0088] As the above-mentioned adhesive, preferably a resin adhesive. As the above-mentioned resin adhesive, there is no particular limitation, and known resin adhesives (thermosetting resins, thermoplastic resins, etc.) used for metal pastes can be used, and preferably a resin component that is fully cured at the temperature when fired is selected. As thermosetting resins, phenolic resins, epoxy resins, unsaturated polyesters, vinyl ester resins, diallyl phthalate, oligoester acrylate resins, xylene resins, bismaleimide triazine resins, furan resins, urea resins, polyurethane resins, melamine resins, silicone resins, acrylic resins, propylene oxide resins, Azine resin, etc., preferably phenolic resin, epoxy resin, Examples of the thermoplastic resin include N-vinylamide, polyamide, polyimide, acrylic resin, ketone resin, polystyrene, polyester, and the like.

[0089] For the copper paste of the present invention, the content of the resin binder can be 0.001 to 10% by mass relative to the mass of the copper particles. When the content of the resin binder is within the above range, the adhesion between the obtained metal film and the substrate becomes better, and a metal film with excellent reliability can be obtained. In order to further exert the above effect, the content of the resin binder is preferably 0.01 to 5% by mass, 0.1 to 2% by mass.

[0090] 2. Method for manufacturing copper paste

[0091] The present invention also relates to a method for producing a copper paste. The method for producing a copper paste comprises a step of dispersing copper particles in a dispersion medium; and a step of adding a reducing agent. In the method for producing a copper paste, when the amount of copper particles used is m1, the average particle size of the copper particles is R1, and the amount of the reducing agent used is m2, formula (1): R1 2 The ratio represented by ×m2 / m1 is 0.008 to 0.8.

[0092] Regarding the copper particles, the dispersion medium, and the reducing agent used in the method for producing the copper paste of the present invention, the contents described in the above-mentioned "1. Copper paste" can be applied.

[0093] The method for producing the copper paste of the present invention may further include a step of adding a binder. Regarding the binder, the contents described in the above "1. Copper paste" can be applied.

[0094] Example

[0095] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the Examples.

[0096] Example 1

[0097] 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) with an average particle size of 1 μm was dispersed and mixed in 1.5 g of distilled water, and 0.4 g of hypophosphorous acid aqueous solution (50%) (Macklin, H815595) (i.e., containing 0.2 g of hypophosphorous acid) was added thereto to prepare a copper paste.

[0098] A groove with a width of 1 mm was formed on a 5 cm square Al2O3 substrate (Taizhou Jingwei Special Ceramics Co., Ltd., alumina ceramic sheet, 50 mm × 50 mm × 1 mm) by a tape with a thickness of 100 μm, and the obtained copper paste was applied, and heated at 120°C in air for 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes, respectively, to form a metal film with a width of 1 mm and a length of 5 cm. The line resistivity of the obtained metal film was measured (using a measuring machine, KEITHLEY, 2000MULTIMETER, contacting the two ends of the linear metal film formed with two terminal probes, and measuring the resistance value). The measurement results are shown in Table 1.

[0099] Example 2

[0100] In Example 2, a copper paste was prepared in the same manner as in Example 1 except that 1.5 g of distilled water as a dispersion medium was changed to 1.5 g of terpineol and 0.05 g of a polyvinyl pyrrolidone resin was further added as a binder.

[0101] A metal film was formed in the same manner as in Example 1 except that the copper paste of Example 2 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0102] Example 3

[0103] In Example 3, a copper paste was prepared in the same manner as in Example 1 except that 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 1 μm was changed to 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 0.5 μm.

[0104] A metal film was formed in the same manner as in Example 1 except that the copper paste of Example 3 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0105] Example 4

[0106] In Example 4, a copper paste was prepared in the same manner as in Example 1 except that 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 1 μm was changed to 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 3 μm.

[0107] A metal film was formed in the same manner as in Example 1 except that the copper paste of Example 4 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0108] Example 5

[0109] In Example 5, a copper paste was prepared in the same manner as in Example 1 except that 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 1 μm was changed to 5.24 g of spherical copper powder (Mitsui Kinzoku, 1100YM) having an average particle size of 5 μm.

[0110] A metal film was formed in the same manner as in Example 1 except that the copper paste of Example 5 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0111] Comparative Example 1

[0112] 1.71 g of spherical copper powder (Anhui Zhonghang Nano, ZH-Cu100) with an average particle size of 0.1 μm was dispersed and mixed in 1.4 g of distilled water, and 0.1 g of hypophosphorous acid aqueous solution (50%) (MACKLIN, H815595) (i.e., containing 0.05 g of hypophosphorous acid) was added thereto to prepare a copper paste.

[0113] A groove with a width of 1 mm was formed on a 5 cm square Al2O3 substrate (Taizhou Jingwei Special Ceramics Co., Ltd., alumina ceramic sheet, 50 mm × 50 mm × 1 mm) by a 100 μ thick tape, and the obtained copper paste was applied, and heated at 120°C in air for 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, and 10 minutes, respectively, to form a metal film with a width of 1 mm and a length of 5 cm. The line resistivity of the obtained metal film was measured (using a measuring machine, KEITHLEY, 2000MULTIMETER, and the two ends of the linear metal film formed with two terminal probes were contacted to measure the resistance value). The measurement results are shown in Table 1.

[0114] Comparative Example 2

[0115] In Comparative Example 2, a copper paste was prepared in the same manner as in Comparative Example 1, except that the amount of the hypophosphorous acid aqueous solution (50%) used was changed from 0.1 g to 0.6 g.

[0116] A metal film was formed in the same manner as in Comparative Example 1 except that the copper paste of Comparative Example 2 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0117] Comparative Example 3

[0118] In Comparative Example 3, a copper paste was prepared in the same manner as in Comparative Example 1, except that the amount of the hypophosphorous acid aqueous solution (50%) used was changed from 0.1 g to 1.06 g.

[0119] A metal film was formed in the same manner as in Comparative Example 1 except that the copper paste of Comparative Example 3 was used. The line resistivity of the obtained metal film was measured. The measurement results are shown in Table 1.

[0120] [Table 1]

[0121]

[0122] Examination of the Results of Examples and Comparative Examples

[0123] (1) Embodiment

[0124] Examples 1 to 5 of the present application are copper pastes including copper particles, a reducing agent, and a dispersion medium.

[0125] In the copper pastes of Examples 1 to 6, when the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, the formula (1) is: R1 2 The ratios shown by ×m2 / m1 are all within the above-mentioned specific range. As a result, in the case of the copper pastes of Examples 1 to 6, metal films (metal films with excellent conductivity) with very low line resistivity can be obtained even when sintered in an air atmosphere at low temperature and for a short time.

[0126] In addition, in the copper pastes of Examples 1 to 6, the average particle size of the copper particles is within the above-mentioned specific range. As a result, the content of the reducing agent can be reduced, and health hazards caused by decomposition of the reducing agent can be improved.

[0127] In Example 2, when a dispersion medium other than water is used and a binder is further added, sintering is performed in an air atmosphere at a low temperature and for a short time to obtain a metal film with very low line resistivity (a metal film with excellent conductivity).

[0128] (1) Comparative Example

[0129] On the other hand, in the copper pastes of Comparative Examples 1 to 3, when the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, the formula (1) is: R1 2 The ratios shown by ×m2 / m1 all deviate from the above-mentioned specific range. As a result, when the copper pastes of Comparative Examples 1 to 3 are sintered in an air atmosphere at a low temperature and for a short time, the line resistivity is infinite or very large, and therefore a metal film with excellent conductivity cannot be obtained.

[0130] In addition, in the copper pastes of Comparative Examples 1 to 3, the average particle size of the copper particles deviates from the above-mentioned specific range. As a result, the content of the reducing agent cannot be reduced, and the health hazards caused by the decomposition of the reducing agent cannot be improved. Moreover, when the average particle size of the copper particles deviates from the above-mentioned specific range, even if a large amount of reducing agent is used, a metal film with excellent conductivity cannot be obtained.

[0131] Industrial Applicability

[0132] According to the above configuration of the present invention, it is possible to provide a copper paste that can achieve excellent electrical conductivity even when sintering is performed in an air atmosphere under low temperature and short time conditions, and a method for producing the copper paste.

[0133] Furthermore, according to the above-described configuration of the present invention, it is possible to provide a copper paste capable of improving health hazards caused by decomposition of a reducing agent in a metal paste, and a method for producing the copper paste.

Claims

1. A copper paste comprising copper particles, a reducing agent and a dispersion medium, When the mass of the copper particles is m1, the average particle size of the copper particles is R1, and the mass of the reducing agent is m2, the ratio represented by the following formula (1) is 0.008 to 0.8, Formula (1): R1 2 ×m2 / m1.

2. The copper paste according to claim 1, wherein The average particle size of the copper particles is 1.0 to 5.0 μm.

3. The copper paste according to claim 1, wherein The content of the reducing agent is 0.1 to 15% by mass relative to the total mass of the copper paste.

4. The copper paste according to claim 1, wherein The copper particles include copper particles coated with copper hydride.

5. The copper paste according to claim 1, wherein The content of the copper hydride coated on the copper particles is 0.1% by mass or more relative to the mass of the copper particles.

6. The copper paste according to claim 1, wherein The reducing agent is a metal hydride and / or hypophosphorous acid.

7. The copper paste according to claim 6, wherein The metal hydride is selected from lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, and calcium hydride.

8. The copper paste according to claim 1, wherein The dispersion medium is a liquid dispersion medium.

9. The copper paste according to claim 8, wherein The liquid dispersion medium is a polar liquid dispersion medium.

10. The copper paste according to claim 9, wherein The polar liquid dispersion medium is selected from water, glyceryl ether, glyceryl ether acetate, alcohol and a mixture thereof.

11. The copper paste according to claim 9 or 10, wherein The polar liquid dispersion medium is water.

12. The copper paste according to claim 1, wherein The content of the dispersion medium is 1 to 100% by mass relative to the mass of the copper particles.

13. The copper paste according to claim 1, further comprising a resin binder.

14. The copper paste according to claim 13, wherein The content of the resin binder is 0.001 to 10% by mass relative to the mass of the copper particles.

15. A method for producing the copper paste according to claim 1, comprising: A step of dispersing copper particles in a dispersion medium; and The process of adding reducing agent, When the amount of copper particles used is m1, the average particle size of the copper particles is R1, and the amount of the reducing agent used is m2, the ratio represented by the following formula (1) is 0.008 to 0.8, Formula (1): R1 2 ×m2 / m1.

16. The method for producing a copper paste according to claim 15, wherein: The average particle size of the copper particles is 1.0 to 5.0 μm.

17. The method for producing a copper paste according to claim 15, wherein: The amount of the reducing agent used is 0.1 to 15% by mass relative to the total mass of the copper paste.

18. The method for producing a copper paste according to claim 15, wherein: The reducing agent is a metal hydride and / or hypophosphorous acid.

19. The method for producing a copper paste according to claim 18, wherein: The metal hydride is selected from lithium aluminum hydride, lithium borohydride, sodium borohydride, lithium hydride, potassium hydride, and calcium hydride.

20. The method for producing a copper paste according to claim 15, wherein: The dispersion medium is a liquid dispersion medium.

21. The method for producing a copper paste according to claim 20, wherein: The liquid dispersion medium is a polar liquid dispersion medium.

22. The method for producing a copper paste according to claim 21, wherein: The polar liquid dispersion medium is selected from water, glyceryl ether, glyceryl ether acetate, alcohol and a mixture thereof.

23. The method for producing a copper paste according to claim 21 or 22, wherein: The polar liquid dispersion medium is water.

24. The method for producing a copper paste according to claim 15, wherein: The amount of the dispersion medium used is 1 to 100% by mass relative to the mass of the copper particles.

25. The method for manufacturing the copper paste according to claim 15, further comprising: The process of adding resin binder.

26. The method for producing a copper paste according to claim 25, wherein: The resin binder is used in an amount of 0.001 to 10% by mass relative to the mass of the copper particles.

Citation Information

Patent Citations

  • Copper hydride nanoparticle, process for producing the same, metallic paste, and article

    WO2009098985A1